Nigeria’s Ambition for the United Nations Security Council within the Context of Historical Antecedents and Domestic Realities: Analysis of the Prospects and Challenges - Ibijola, Ibijola (Advances in Social Sciences Research Journal, 2015)
This paper draws a linkage between Nigeria’s roles during the struggle against colonialism in Africa and the country’s quest for a permanent seat on the United Nations Security Council (UNSC). The paper argues that Nigeria’s past roles in African decolonization process especially its efforts toward the eradication of aparthied and colonialism in Southern Africa and its current domestic condition have both positive and negative implications for the country’s ambition. The paper submits that Nigeria’s greatest credentials for the UNSC seat lie not in its records of service to the African cause but in the combination of that record with an appreciable domestic condition which is epitomized by good governance, protection of human rights, sound and enduring democratic institutions, dedicated political leadership, zero tolerance for corruption and functional judiciary in the current context. Nigeria’s success also depends on ensuring security on the home front, tackling mass impoverishment and working towards a robust economy.